2020
DOI: 10.3390/ijms21072530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pharmacological Inhibition of the Catalytic Activity of Phosphatases of Regenerating Liver in Early T Cell Receptor Signaling Dynamics and IL-2 Production

Abstract: We have previously shown the delivery of phosphatase of regenerating liver-1 (PRL-1) to the immunological synapse (IS) and proposed a regulatory role of the catalytic activity of PRLs (PRL-1, PRL-2 and PRL-3) in antigen-induced IL-2 production. Nonetheless, the expression in T cells and delivery to the IS of the highly homologous PRL-3, as well as the role of the catalytic activity of PRLs in antigen-induced early signaling, has not been investigated. Here, the expression of PRL-3 protein was detected in prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
(50 reference statements)
0
10
1
Order By: Relevance
“…Surprisingly, the resistant cell lines did demonstrate a reduced ability to generate colonies in vitro in the absence of JMS-053 exposure. In OvCa loss of colony forming ability is greatly influenced by the growth factors and cytokines in the microenvironment and PTP4A3 has been shown to be highly involved in growth factor and cytokine processing and release (Yang et al, 2017;Aguilar-Sopena et al, 2020). Interestingly, we found no marked differences in the PTP4A3 protein levels in the cells with acquired JMS-053 resistance.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Surprisingly, the resistant cell lines did demonstrate a reduced ability to generate colonies in vitro in the absence of JMS-053 exposure. In OvCa loss of colony forming ability is greatly influenced by the growth factors and cytokines in the microenvironment and PTP4A3 has been shown to be highly involved in growth factor and cytokine processing and release (Yang et al, 2017;Aguilar-Sopena et al, 2020). Interestingly, we found no marked differences in the PTP4A3 protein levels in the cells with acquired JMS-053 resistance.…”
Section: Discussioncontrasting
confidence: 50%
“…PTP4A3 controls the phosphorylation status of a remarkable number of intracellular signaling proteins, which alters transcription, receptor signaling dynamics, and cytokine release (Aguilar-Sopena et al, 2020), although its direct substrates have not been firmly established. One study (Chong et al, 2019) demonstrated PTP4A3 participates with Signal Transducer and Activator of Transcription 3 (STAT3) in a feedforward loop with SHP-2 phosphatase (also known as PTPN11) in multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphatase of regenerating liver-1 is enriched at the plasma membrane in different cellular models and has been proposed to localize to the ER (Wang et al, 2002), as well as in early endosomes few minutes after endocytosis and in the recycling compartment (Zeng et al, 2000). Recently, we have shown the distribution of PRL-1 and PRL-3 to the CD71-containing recycling compartment in lymphoid cells (Castro-Sanchez et al, 2018;Aguilar-Sopena et al, 2020). These results suggested that, in lymphocytes, the recycling compartment might contribute to a rapid plasma membrane replenishment of endocytosed PRL-1 in the same way it sustains surface expression of CD71 (Klausner et al, 1983).…”
Section: Gfp-prl-1 Membrane Accumulation Is Resistant To Brefeldin a mentioning
confidence: 99%
“…However, several reports have demonstrated that the use of GFP may impact the biological activity of fusion proteins (45)(46)(47), including cellular localization (48). Many past studies examining PRL-3 localization, which have primarily characterized PRL-3 as membrane exclusive due to the presence of a C-terminal prenylation, have utilized N-terminal tags such as Myc (20,49) or EGFP (49,50). We wanted to use our PRL-3 nanobodies to determine if tagged versions of PRL-3 localize differently than wild-type, untagged PRL-3.…”
Section: An N-terminal Tag Impacts Prl-3 Localization In Hct116 Colorectal Cancer Cellsmentioning
confidence: 99%